THE FEMINISTIC COMPONENT IN THEFEMALE DETECTIVE NOVEL: THE COMPARATIVE ASPECT (ON THE BASIS OF WORKS BY IRENE ROZDOBUDKO “THE DOUBLE GAME IN FOUR HANDS” AND “GAUDY NIGHT”BY DOROTHY SAYERS) - Huliak, T. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article deals with the feminist component in the detective novels «The Double Game in Four Hands» by I. Rozdobudko and «Gaudy Night» by D. Sayers. Its dominant features are distinguished: original female images and women's writing which is manifested through the detailing and usage of parenthetical constructions. The common and distinctive features of the use of the feminist component in the Ukrainian and English female detective discourse are described. The similarity and difference in the images of Musya Gurchyk and Harriet Vane who are the expressions of the creative method of detective writers are analyzed. The emotional and detailing functions of the parenthetical constructions are described. It is emphasized that the feminist component plays an important role in the creation of the genre of the female detective novel.